COMT rs4680 Met is not always the 'smart allele': Val allele is associated with better working memory and larger hippocampal volume in healthy Chinese. (20th February 2013) - Wang, Y.; Li, J.; Chen, C.; Chen, C.; Zhu, B.; Moysis, R. K.; Lei, X.; Li, H.; Liu, Q.; Xiu, D.; Liu, B.; Chen, W.; et al.
<x xml:space="preserve">Abstract</x> Catechol‐O‐methyltransferase (COMT) Val158Met (rs4680) polymorphism plays a crucial role in regulating brain dopamine level. Converging evidence from Caucasian samples showed that, compared with rs4680 Val allele, the Met allele was linked to lower COMT activity, which in turn was linked to better cognitive performance such as working memory (WM) and to a larger hippocampus (a brain region important for WM). However, some behavioral studies have shown that the function of rs4680 appears to vary across different ethnic groups, with Chinese subjects showing an opposite pattern as that for Caucasians (i.e. the Val allele is linked to better cognitive functions related to WM in Chinese). Using a sample of healthy Han Chinese college students (ages from 19 to 21 years), this study investigated the association of COMT Val158Met genotype with behavioral data on a two‐back WM task (n = 443, 189M/254F) and T1 MRI data (n = 320, 134M/186F). Results showed that, compared to the Met allele, the Val allele was associated with larger hippocampal volume (the right hippocampus: β = −0.118, t = −2.367, P = 0.019, and the left hippocampus: β = −0.099, t = −1.949, P = 0.052) and better WM performance (β = −0.110, t = −2.315, P = 0.021). These results add to the growing literature on differentiated effects of COMT rs4680 polymorphism on WM across populations and offer a brain structural mechanism for such population‐specific genetic effects.